FDG uptake tracks the oxidative damage in diabetic skeletal muscle: An experimental study - Matteo Bauckneht; Vanessa Cossu; Patrizia Castellani; Patrizia Piccioli; Anna Maria Orengo; Laura Emionite; Francesco Di Giulio; Maria Isabella Donegani; Alberto Miceli; Stefano Raffa; Anna Borra; Selene Capitanio; et al. (Elsevier, 2020)
Objectives: The present study aims to verify the relationship between glucose consumption and uptake of 18F-2-deoxy-glucose (FDG) in the skeletal muscle (SM) of experimental models of streptozotocin-induced diabetes mellitus (STZ-DM). Methods: The study included 36 Balb/c mice. Two weeks after intraperitoneal administration of saline (control group, n = 18) or 150 mg streptozotocin (STZ-DM group, n = 18), the two cohorts were submitted to an oral glucose tolerance test and were further subdivided into three groups (n = 6 each): untreated and treated with metformin (MTF) at low or high doses (10 or 750 mg/kg daily, respectively). Two weeks thereafter, all mice were submitted to dynamic micro-positron emission tomography (PET) imaging after prolonged fasting. After sacrifice, enzymatic pathways and response to oxidative stress were evaluated in harvested SM. Results: On PET imaging, the FDG uptake rate in hindlimb SM was significantly lower in nondiabetic mice as compared with STZ-DM-untreated mice. MTF had no significant effect on SM FDG uptake in untreated mice; however, its high dose induced a significant decrease in STZ-DM animals. Upon conventional analysis, the SM standard uptake value was higher in STZ-DM mice, while MTF was virtually ineffective in either control or STZ-DM models. This metabolic reprogramming was not explained by any change in cytosolic glucose metabolism. By contrast, it closely agreed with the catalytic function of hexose-6P-dehydrogenase (H6PD; i.e., the trigger of a specific pentose phosphate pathway selectively located within the endoplasmic reticulum). In agreement with this role, the H6PD enzymatic response to both STZ-DM and MTF matched the activation of the NADPH-dependent antioxidant responses to the increased generation of reactive oxygen species caused by chronic hyperglycemia. Ex vivo analysis of tracer kinetics confirmed that the enhanced SM avidity for FDG occurred despite a significant reduction in glucose consumption, while it was associated with increased radioactivity transfer to the endoplasmic reticulum. Conclusions: These data challenge the current dogma linking FDG uptake to the glycolytic rate. They instead introduce a new model considering a strict link between the uptake of this glucose analog, H6PD reticular activity, and oxidative damage in diabetes, at least under fasting condition. Keywords: Fluorodeoxyglucose, Hexose-6P-dehydrogenase, Diabetes, Skeletal muscle, Oxidative stress